The linear relationship between systolic pulmonary artery pressure and mean pulmonary artery pressure is maintained regardless of autonomic or rhythm disturbances. Issue 1 (December 2016) - Vanden Eynden, Frédéric; Racapé, Judith; Vincent, Jame; Vachiéry, Jean-Luc; Bové, Thierry; Van Nooten, Guido
Abstract Background In the pulmonary circulation, there is a linear relationship between systolic pulmonary arterial pressure (SPAP) and mean pulmonary arterial pressure (MPAP). The aim of this study was to determine the passive or active nature of this mechanism by exploring the relationship in patients with and without autonomic rhythm control of the heart and pulmonary circulation. Methods Pulmonary arterial pressure recordings from non-transplanted patients and patients with heart transplants or double lung transplants were retrospectively reviewed. The relationships between systolic, diastolic, and mean pulmonary arterial pressures were explored. Results A linear relationship was observed between the SPAP and MPAP, whether patients were paced (MPAP = 0.56 SPAP + 3.86 mmHg, r 2  = 0.889), treated with inotropes (MPAP = 0.55 SPAP + 5.52 mmHg, r 2  = 0.947) or pulmonary vasodilators (MPAP = 0.58 SPAP + 2.41 mmHg, r 2  = 0.927), were exercising (MPAP = 0.61 SPAP + 1.18 mmHg, r 2  = 0.967), had a heart transplant (MPAP = 0.66 SPAP +0.87 mmHg, r 2  = 0.849), a double lung transplant (MPAP = 0.7 SPAP +0.48 mmHg, r 2  = 0.915), or no intervention (MPAP = 0.59 SPAP +1.75 mmHg, r 2  = 0.937). Conclusion We demonstrate that the linear relationship between SPAP and MPAP remains in several situations. Therefore, we conclude that the underlying mechanism is a passive consequence of the elastic properties of the cardiopulmonary unit.